Case Report: A Case of Adult Methylmalonic Acidemia With Bilateral Cerebellar Lesions Caused by a New Mutation in MMACHC Gene - Wang, Shengnan; Wang, Xu; Xi, Jianxin; Yang, Wenzhuo; Zhu, Mingqin (Frontiers in Neurology, 2022)
Methylmalonic acidemia (MMA) is a severe heterogeneous disorder of methylmalonate and cobalamin (Cbl; vitamin B12) metabolism with poor prognosis. Around 90% of reported patients with methylmalonic acidemia (MMA) are severe infantile early-onset, while late-onset MMA has been rarely reported. Few reported late-onset MMA patients presented with atypical clinical symptoms, therefore, often misdiagnosed if without family history. Herein, we report a 29-year-old female who was admitted to our hospital due to symptoms manifested as encephalitis. The brain MRI showed symmetrical bilateral cerebellar lesions with Gd enhancement. Laboratory test showed significantly elevated levels of homocysteine and methylmalonic acid. Genetic analysis identified a novel homozygous mutation (c.484G>A; p.Gly162 Arg) in the MMACHC gene. The patient was diagnosed as MMA, and her symptoms improved dramatically with intramuscular adenosine cobalamin treatment. In conclusion, for patients with symmetrical lesions in the brain, the possibility of metabolic diseases should be considered, detailed medical and family history should be collected, metabolic screening tests as well as gene tests are necessary for correct diagnosis. The mutation diversity in MMACHC gene is an important factor leading to the heterogeneity of clinical manifestations of MMA patients.